Depletion-restitution therapy for autoimmune rheumatic diseases. Part 1. Fundamental prerequisites and efficacy of modern treatment technologies: anti-B-cell drugs and CAR-T therapy - A. M. Lila; A. L. Maslyanskiy; D. A. Dibrov; A. V. Torgashina; E. G. Zotkin; M. Yu. Samsonov (Современная ревматология)
The key element in the pathogenesis of systemic autoimmune rheumatic diseases is the breakdown of immunological tolerance and the formation of a pool of autoreactive cells. This leads to uncontrolled activation of the effector arm of cellular (T-lymphocytes) and humoral (B-lymphocytes and plasma cells) immunity, proliferation of autoreactive clones, and the formation and persistence of immunological memory cells. In this process, T-cells, B-cells, and plasma cells of immunological memory, in interaction with a complex of pathogenic signals from the microenvironment, ensure the stability and adaptability of the developing inflammatory process.In modern clinical practice, the prevailing approach to prescribing medications is the "therapeutic pyramid" strategy, which involves gradual escalation of treatment until remission is achieved. This approach does not address the mechanisms of immunological tolerance and, as a result, requires lifelong therapy and is associated with numerous adverse effects.The term “depletion-restitution therapy” is proposed (from English “depletion” – exhaustion; and Latin “restitutio ad integrum” – restoration to the original state, complete recovery) to describe an alternative approach. This approach is characterized by methods based on massive, shortterm cytotoxic impact, leading to profound reduction of pathogenic autoreactive cellular clones, followed by repopulation with "naive" cellular elements. Consequently, this restores tolerance mechanisms and enables the formation of ultra-long, drug-free remissions.Currently, the principles of depletion-restitution therapy have already been integrated into oncology, hematology, and neurology. Among the most promising potential targets for such therapy in rheumatology are the effectors of the humoral immune system: B-cells, plasmablasts, and plasma cells. At the present stage, the most promising methods for implementing this approach are CAR-T cells and therapeutic bispecific monoclonal antibodies.